(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indian democracy is one of the largest and most diverse in the world, characterized by regular elections, with a multi-party system, and a robust constitution that guarantees fundamental rights to its citizens. India, often referred to as the Mother of Democracy, stands as an outstanding example for democratic ideals and values in the world. The foundational principles of Indian democracy have evolved over centuries, drawing from ancient cultural and philosophical roots. India adopted parliamentary form of government since its independence and faced several challenges to rebuild its system on the basis of Democratic principles. But since few decades India is experiencing Democratic deficits. The social and religious polarization is fuelled by various factors, including identity politics, historical grievances, economic disparities, and external influences. It manifests in communal tensions, intolerance, and the marginalization of certain groups based on religion, caste, or ethnicity.